Platelet aggregability in relation to impaired consciousness after head injury. - Vecht, C J (1975)
ADP-induced platelet aggregation was studied for up to six weeks in 34 patients with head injuries. The patients were divided into three groups according to the degree of impaired consciousness assessed by a clinical coma scale, and change in platelet aggregation was related to the coma score. Platelet aggregation was markedly reduced in all eight patients dying within 24 hours of injury. All 17 patients who remained unconscious for four days or more showed decreased platelet aggregation up to nine days after admission, the most marked effect being on the second day. Platelet function in this group returned to normal within 16 days. Nine patients with only slightly impaired consciousness also showed subnormal platelet aggregation during the first few days with a return to normal by the fourth day. Platelet counts remained within normal limits in all groups. We suggest that during coma following head injury brainstem dysfunction induces neurohumoral changes in the blood which are responsible for a decrease in platelet function.